Money Laundering and Legal Globalization: Where Does the United States Stand on This Issue? - Ellen S. Podgor (Washington University Global Studies Law Review, 2006)
In this book review, Ellen S. Podgor offers a review of Heba Sham, Legal Globalization: Money Laundering Law and Other Cases from the Sir Joseph Gold Memorial Series.
Keywords: Money laundering; Globalization; Prosecution -- Decision making; Jurisdiction (International law)